FINAL PROJECT CONSULTATION INFORMATION SYSTEM INTEGRATED NOTIFICATION SYSTEM BASED ON SMS GATEWAY - Dedi Satria; Zulfan Zulfan; Munawir Munawir; Dewi Mulyati (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2018)
The process of final project research consultations is now often done by making a schedule to meet with supervisors within the time set by students and supervisors. It is known that the consultation process by the way it is done now still has problems from the effectiveness of student research time and the distance between the research center and the location of the supervisor. With these problems resulted in students not being timely in conducting research consultations with their supervisors. Therefore, a system is needed that can provide a system of research consultations remotely using internet facilities that are integrated with the consultation notification system via the SMS Gateway. The methodology is built using the phases of context diagrams, data flow diagrams and entity relationships. The system is built using PHP programming, mySQL database and Gammu. The results of the final project consultation information system research integrated with the notification system using the SMS Gateway have produced several tables and forms, namely student forms, lecturer forms, consultation forms and document forms. The form has been able to provide a remote consultation system using web media and has been able to provide notification notifications to students and lecturers regarding the consultation status using the SMS gateway service. It is expected that this information system can facilitate students and lecturers in conducting more effective and efficient consultations.